Guanylate-binding proteins 2 and 5 exert broad antiviral activity by inhibiting furin-mediated processing of viral envelope proteins - Braun, Elisabeth; Hotter, Dominik; Wombacher, Rebecka; Fackler, Oliver Till (Cell reports, 2019)
Summary - Guanylate-binding protein (GBP) 5 is an interferon (IFN)-inducible cellular factor reducing HIV-1 infectivity by an incompletely understood mechanism. Here, we show that this activity is shared by GBP2, but not by other members of the human GBP family. GBP2/5 decrease the activity of the cellular proprotein convertase furin, which mediates conversion of the HIV-1 envelope protein (Env) precursor gp160 into mature gp120 and gp41. Because this process primes HIV-1 Env for membrane fusion, viral particles produced in the presence of GBP2/5 are poorly infectious due to increased incorporation of non-functional gp160. Furin activity is critical for the processing of envelope glycoproteins of many viral pathogens. Consistently, GBP2/5 also inhibit Zika, measles, and influenza A virus replication and decrease infectivity of viral particles carrying glycoproteins of Marburg and murine leukemia viruses. Collectively, our results show that GPB2/5 exert broad antiviral activity by suppressing the activity of the virus-dependency factor furin.